„Uwięzione dzieciństwo” – bariery procesu socjalizacji - Chojecka, Jana (Wydawnictwo Naukowe UAM, 2013)
The most popular punishment in response to a crime is imprisonment. We can observe increasing rates of the prison population all over the world. Women are the fastest-growing segment of the prison population. We have to remember that when we impose a penalty on adult offenders, there can be covert victims of incarceration. Children whose parents have been arrested and incarcerated face various type of difficulties. The aim of this paper is to address short- and long-term outcomes of parents’ imprisonment and to show programs which are conducted for prisoners and their children in order to minimize the trauma of separation.
“Imprisoned Childhood” – Barriers to Socialization
Keywords: children of incarcerated parents; model of intergenerational transmission of offending; effects of parental incarceration; programs for children of incarcerated parents